Costa Rica: Crisis, adjustment policies and rural development - Juan M. Villasuso (CEPAL Review, 1987)
At the end of the 1970s Gista Rica was hit by the worst crisis in its history. The coffee boom ended abruptly in 1978, causing a sizeable drop in export earnings. Furthermore, public spending increased sharply, generating a deficit which was financed largely by short-term foreign borrowing. In addition, the exchange-rate slippage, in conjunction with the deterioration in the terms of trade, brought about the exhaustion of monetary reserves, and this situation was exacerbated even further by the higher interest rates in the international market.